Relationship Testosterone with the development of Alzheimer's disease in men with diabetes - Asra'a I. Al-Taii; Ektefa'a A; Ranen S. Rodan (Tikrit Journal of Pure Science, 2023)
That diabetes is a serious disease is widespread, a gate opens many health problems such as heart disease, kidney addition to that, it is a serious alarm for the brain and nervous start from the loss of concentration and poor memory through  decline into the abyss of Alzheimer's.The study included 65 blood sample, which included the first group (25) a sample of the blood of healthy people, while the second group are (40) blood samples from people with diabetes were (20) patients with the blood of diabetes patients with Alzheimer's sample.